2018
DOI: 10.1002/er.4076
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the external electrical thermal and dynamic power characteristics of alkaline water electrolyzer

Abstract: Summary As hydrogen production with a water electrolyzer is an effective way for renewable energy consumption, understanding the external electrical characteristics of water electrolyzer is of great significance for the modeling and simulation, system configuration, and control strategy of the system for hydrogen production by renewable energy. However, there are relatively fewer studies in this area. This paper presents the establishment of an experimental platform to conduct an experimental study on the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…The most-used electrolyte for alkaline water electrolysis is an aqueous solution of potassium hydroxide (KOH) with 20 to 30 wt.% KOH, as the specific conductivity is optimal at the typical temperature range from 50 to 80 • C [25]. A cheaper alternative would be a diluted sodium hydroxide solution (NaOH), which has a lower conductivity [52].…”
Section: Cell Design and Cell Voltagementioning
confidence: 99%
See 2 more Smart Citations
“…The most-used electrolyte for alkaline water electrolysis is an aqueous solution of potassium hydroxide (KOH) with 20 to 30 wt.% KOH, as the specific conductivity is optimal at the typical temperature range from 50 to 80 • C [25]. A cheaper alternative would be a diluted sodium hydroxide solution (NaOH), which has a lower conductivity [52].…”
Section: Cell Design and Cell Voltagementioning
confidence: 99%
“…At lower energy demands, hydrogen can be produced and converted back into energy when it is needed. As conventional alkaline water electrolyzers are designed for operation at constant conditions, occurring fluctuations may be damped by additional energy storage devices like batteries, supercapacitors, or flywheels [25,28,82]. When excess energy is available, this energy storage can be charged to be fully available when needed.…”
Section: Hydrogen Energy System and Power Grid Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the advantages of the new two non‐independent modules are obvious. For the traditional single module, the test object in Shen et al is used as an example, and the basic performance parameters of the device are shown in Table . Modules A and B are the same in structure and capacity.…”
Section: A Case Studymentioning
confidence: 99%
“…In the early stage, researchers established a test platform with 2 traditional AWEs manufactured by Suzhou Jing Li Hydrogen Equipment Co, Ltd as research objects and carried out studies on the static and dynamic volt-ampere characteristics of AWE and its preliminary power regulation characteristics. 26 Test object 1 was in multipole series with the number in series (n s ) being 10, the working temperature range 50°C to 80°C, the working voltage range 16 to 21 V, and the test environment temperature T c = 6°C. Test object 2 was also in multipole series, with the number of series (n s ) being 8, the working temperature range 50°C to 80°C, the working voltage range 12.8 to 18.4 V, and the test environment temperature T c = 20°C.…”
Section: Overviewmentioning
confidence: 99%